Experimental and numerical investigation of the microwave dielectric properties of the MgTiO3 ceramic matrix added with CaCu3Ti4O12 - Oliveira,P.W.S. (2017)
Abstract This paper describes an experimental and numerical investigation of the dielectric resonators based on the MgTiO3 ceramic matrix, which relates to their dielectric properties in microwave. The resonators are compounds of the MgTiO3 added with 4, 6, 8, 10 and 12 wt% of the CaCu3Ti4O12. The manufacturing process of the resonators is based on the solid-state method. The properties of the permittivity and dielectric loss are elucidated using the Hakki and Coleman´s method. The experimental measurements of the dielectric resonators, acting as antennas, provide some results as return loss, gain, efficiency, bandwidth and input impedance. These results are coherent with the numerical investigation. The addition of the perovskite CaCu3Ti4O12 in the MgTiO3 ceramic matrix increased the value of the dielectric constant and it was obtained a higher value of 21.01 for the sample MgTiO3 added with 12% CaCu3Ti4O12. The temperature coefficient of resonant frequency (τf) was measured for all the samples and the best value obtained was 9.62 ppm/°C for the sample MgTiO3 added with 12% CaCu3Ti4O12. The material duly proposed, shows to be promising for applications as dielectric antennas and this study point out that it is possible to obtain a dielectric resonator antenna (DRA) with a temperature coefficient of resonant frequency close to zero.